Staying Optimistic: The Trials and Tribulations of Leibnizian Optimism - Lloyd Strickland (Journal of Modern Philosophy)
The oft-told story of Leibniz’s doctrine of the best world, or optimism, is that it enjoyed a great deal of popularity in the eighteenth century until the massive earthquake that struck Lisbon on 1 November 1755 destroyed its support. Despite its long history, this story is nothing more than a commentators’ fiction that has become accepted wisdom not through sheer weight of evidence but through sheer frequency of repetition. In this paper we shall examine the reception of Leibniz’s doctrine of the best world in the eighteenth century in order to get a clearer understanding of what its fate really was. As we shall see, while Leibniz’s doctrine did win a good number of adherents in the 1720s and 1730s, especially in Germany, support for it had largely dried up by the mid-1740s; moreover, while opponents of Leibniz’s doctrine were few and far between in the 1710s and 1720s, they became increasing vocal in the 1730s and afterwards, between them producing an array of objections that served to make Leibnizian optimism both philosophically and theologically toxic years before the Lisbon earthquake struck.